2016
DOI: 10.1108/jmhtep-07-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of awareness level knowledge and understanding framework personality disorder training with mental health staff: impact on attitudes and clinical practice

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…One of the major limitations of this evaluation is in the reduced follow up rates. The attrition at follow up in this study is disappointingly consistent with the other studies that evaluated KUF (Lamph et al, 2014;Davies et al, 2014 andEbrahim et al, 2015). Without a dedicated research team or some motivating factors for delegates to complete the follow up, high levels of attrition can be expected.…”
Section: Limitationssupporting
confidence: 79%
See 1 more Smart Citation
“…One of the major limitations of this evaluation is in the reduced follow up rates. The attrition at follow up in this study is disappointingly consistent with the other studies that evaluated KUF (Lamph et al, 2014;Davies et al, 2014 andEbrahim et al, 2015). Without a dedicated research team or some motivating factors for delegates to complete the follow up, high levels of attrition can be expected.…”
Section: Limitationssupporting
confidence: 79%
“…Face to face training in this subject has also been made available in various formats to those working in this geographical area. Previous evaluations of face to face training have focused on mental health professionals (Davies et al, 2014), mixed multi-agency workers (Lamph et al, 2014) and one external evaluation with mental health professionals (Ebrahim et al, 2015). These papers will be used to provide comparisons in the evaluation of this project.…”
mentioning
confidence: 99%
“…The participants in this study ( Table 2, PD-KASQ) reported lower levels of understanding, perceived capability, and positive emotional response to PD than the pre-training scores for mental health service staff (mental health nurses and occupational therapists working in inpatient and community settings) reported by Ebrahim et al (2016). In addition, they reported lower levels of positive therapeutic engagement, and more emotional difficulties (Table 2, STAR-C), than the community mental health staff group reported by Catty et al (2012).…”
Section: Resultsmentioning
confidence: 61%
“…carer involvement; staff supervision). Such training may also have a broader impact on staff attitudes towards PD and staff perceptions of their ability to care for these individuals (Ebrahim, Robinson, Crooks, Harenwall & Forsyth; ).…”
Section: Discussionmentioning
confidence: 99%
“…Missing information was sought by contacting authors using the email addresses provided and alternative email addresses found online. There remain missing data regarding study setting (Polnay, MacLean, Lewington, & Patrick, 2015;Shanks, Pfohl, Blum, & Black, 2011), professional role of participants (Lamph et al, 2014;Lamph, Sampson, Smith, Williamson, & Guyers, 2018), use of psychological model (Commons-Treloar & Lewis, 2008;Lamph et al, 2018;Miller & Davenport, 1996), whether the intervention included a taught skills component (Davies, Sampson, Beesley, Smith, & Baldwin, 2014;Ebrahim, Robinson, Crooks, Harenwall, & Forsyth, 2016;Lamph et al, 2014), and whether videos included PPE (Keuroghlian et al, 2016;Polnay et al, 2015;Shanks et al, 2011). For one study standard deviations were not available (Ebrahim et al, 2016).…”
Section: Resultsmentioning
confidence: 99%